High-stability conducting polymer-based conformal electrodes for bio-/iono-electronics. (March 2022) - Yao, Bowen; Scalco de Vasconcelos, Luize; Cui, Qingyu; Cardenas, Anne; Yan, Yichen; Du, Yingjie; Wu, Dong; Wu, Shuwang; Hsiai, Tzung K.; Lu, Nanshu; Zhu, Xinyuan; He, Ximin
Graphical abstract: Abstract: Compared to conventional rigid electronics, polymer-based soft electronics conformal to organisms of irregular shapes have emerged as the next-generation devices, especially benefiting long-term bio-interface interactions that avoid mechanical mismatch and consequent adverse immune responses. Highly conductive poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) has become a promising candidate for building soft conductors/electrodes due to its good conductance, tunable mechanical stiffness, good biocompatibility and facile fabrication into various structures. However, their high instability towards alkaline, reductants and applied voltage has not yet been fully addressed, which inevitably leads to deteriorated performance in complex physiological environments or weather conditions (e.g., humidity). Such intolerances are rooted in unstable electronic/molecular structures of PEDOT caused by de-doping. Besides the low electrical stability, PEDOT:PSS films also exhibit an impaired overall conductance due to its phase separation into PSS-rich and PEDOT-rich domains. Herein, a general and effective coating strategy is proposed, based on a mechanism of simultaneous molecular rejection and electron conjugation, to improve the stability and boost the conductance. Specifically, a reduced-graphene-oxide (rGO) thin layer can not only protect PEDOT: PSS from being de-doped by alkali, bio-reductants and applied voltage through molecular rejection, to maintain its conductivity and ensure stable functions, but also further boost the overall conductance through a bridging effect with its large conjugated domain. This strategy is compatible with various material fabrication techniques, including blade-coating, dip-coating and extrusion-based printing techniques, enabling the fabrication of conductors/electrodes with different structures. Finally, the advantages of excellent stability and high conformability of the composite films as soft conductors have been demonstrated through practical applications in tissue stimulation, electrophysiological recording and proprioceptive hydrogel skins, exhibiting great promise in bio/iono-electronics and human–machine interactions.